Moonstruck [videorecording (Blu-Ray)] - Shanley, John Patrick; Cher, 1946-; Cage, Nicolas, 1965-; Gardenia, Vincent; Dukakis, Olympia; Aiello, Danny, 1933-2019; Watkin, David, 1925-2008; Hyman, Dick, 1927- (Metro-Goldwyn-Mayer Studios Inc., 2010)
An "unlucky in love" Italian-American widow just weeks away from her wedding falls for her fiance's younger brother.